The daydreams - Hankin, Laura (Berkley, 2023)
"A deliciously entertaining novel about the stars of a popular teen show from the early 2000s-and the reunion special, thirteen years after their scandalous flameout, that will either be their last chance at redemption, or destroy them all for good. Back in 2004, The Daydreams had it all: a cast of innocent-seeming teenagers acting and singing their hearts out, amazing ratings, and a will-they-or-won't-they romance that steamed up fan fiction forums. Then, during the live season two finale, it all imploded, leaving everyone scrambling to understand why. Afterward, the four stars went down very different paths. Kat is now a lawyer in DC. Liana is the bored wife of a famous athlete. Noah, the show's golden boy, emerged unscathed and is poised to become a household name. And Summer, the object of Noah's fictional (and maybe real-life) affections, is the cautionary tale. But then the fans demand a reunion special. The stars all have private reasons to come back: forgiveness, revenge, a second chance with a first love. But as they tentatively rediscover the magic of the original show, old secrets threaten to resurface-including the real reason behind their downfall. Will this reunion be a chance to make things right? Or will it be the biggest mess the world has ever seen? No matter what, the ratings will be wild"--